Diacerein for the treatment of rheumatoid arthritis in patients with inadequate response to methotrexate: a pilot randomized, double-blind, placebo-controlled add-on trial - Worawit Louthrenoo (2019)
© 2019, International League of Associations for Rheumatology (ILAR). Objective: To evaluate the efficacy and safety of diacerein in patients with rheumatoid arthritis (RA) who are methotrexate inadequate responders (MTX-IR). Method: In this pilot, multicenter, double-blind, placebo-controlled trial, MTX-IR RA patients were randomized to either diacerein or matching placebo as add-on treatment to MTX for 24 weeks. Efficacy and safety were evaluated every 4 weeks until week 28. Primary and secondary efficacy endpoints were the percentage of patients achieving the ACR20 criteria and a moderate EULAR response at week 24, respectively. Results: Forty patients were equally randomized to both study treatments; 16 and 19 participants completed the study in the diacerein and the placebo arms, respectively. Baseline characteristics were similar in both groups, except that tender joint count, DAS28-ESR score, and non-steroidal anti-inflammatory drug consumption were higher in the placebo arm. The ACR20 response at week 24 was similar in the diacerein and placebo groups (65% vs 45%, P =.20). However, treatment response according to the EULAR criteria was better in patients taking diacerein (75% vs 25% of moderate response, P =.002). In the 35 patients with assessments through week 28, diacerein was superior to placebo in ACR20 at weeks 24 and 28 (both 81% vs 47%, P =.04). Incidence of adverse events was comparable in both arms, with only chromaturia being more common with diacerein than placebo (40% vs 10%, P =.03). Conclusions: These preliminary results show the potential benefits of diacerein on pain, joint function, and disease activity in MTX-IR RA patients. Trial registration: ClinicalTrials.gov Identifier: NCT01264211Key Points• Diacerein has shown positive effects on rheumatoid arthritis symptoms.• A good safety profile of diacerein has been observed when it was administered as add-on therapy to methotrexate in patients with rheumatoid arthritis.